2009
DOI: 10.1074/jbc.m807259200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Delineation of the Pathways Mediated by Bid and JNK in Tumor Necrosis Factor-α-induced Liver Injury in Adult and Embryonic Mice

Abstract: Tumor necrosis factor-␣ (TNF␣)-induced hepatocyte death and liver injury can be mediated by multiple mechanisms, which could be evaluated by different animal models. Previous studies have defined the importance of Bid in mitochondrial apoptosis activation in adult mice treated with lipopolysaccharides in the presence of galactosamine (GalN), which suppresses NF-B activation, but not in embryonic mice in which NF-B activation is suppressed by genetic deletion of p65RelA. JNK has also been found important in TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Similarly, pretreatment of mice with JNK inhibitors rescued the animals from the development of severe liver injury. Moreover, TNFα-induced activation of JNK correlated with liver damage after injection of ConA, and JNK inhibitors could block hepatocyte cell death induced by ConA [57,58]. In contrast to these observations, it was recently demonstrated that JNK is critically required for TNFα expression in hematopoietic cells and it is not mandatory for TNFα-triggered hepatocyte cell death during the development of liver damage [59].…”
Section: Tnf Receptor/ligand Interactions In Liver Injurymentioning
confidence: 65%
“…Similarly, pretreatment of mice with JNK inhibitors rescued the animals from the development of severe liver injury. Moreover, TNFα-induced activation of JNK correlated with liver damage after injection of ConA, and JNK inhibitors could block hepatocyte cell death induced by ConA [57,58]. In contrast to these observations, it was recently demonstrated that JNK is critically required for TNFα expression in hematopoietic cells and it is not mandatory for TNFα-triggered hepatocyte cell death during the development of liver damage [59].…”
Section: Tnf Receptor/ligand Interactions In Liver Injurymentioning
confidence: 65%
“…They also indicate that a mitochondrial activation loop that produces ROS, rather than only continuous TNFR signaling, sustains JNK activation. Upon TNF stimulation, Bid, a BH3-only protein, is cleaved by caspase-8 in a JNK2-dependent manner 27,30 . The cleaved Bid translocates to the mitochondrial outer membrane to induce cytochrome-c release and caspase-9/caspase-3 activation, resulting in TNF-mediated hepatocyte death 27,31 .…”
Section: Tnf-mediated Hepatocyte Death and Liver Injurymentioning
confidence: 99%
“…The cleaved Bid translocates to the mitochondrial outer membrane to induce cytochrome-c release and caspase-9/caspase-3 activation, resulting in TNF-mediated hepatocyte death 27,31 . The requirement for Bid in hepatocyte death has been demonstrated by the resistance of Bid −/− mice to TNF-induced liver injury 30 .…”
Section: Tnf-mediated Hepatocyte Death and Liver Injurymentioning
confidence: 99%
“…These analyses, however, await confirmation in animal models, including models of liver injury. Analyses of Jnk1 −/− and Jnk2 −/− mice challenged with either LPS/GalN or ConA/GalN, however, have recently suggested that activation of Bid is independent of JNK activity, suggesting a parallel role for Bid and JNK signalling in mediating TNFα-induced liver injury (Ni et al, 2009). …”
Section: Mechanisms Of Jnk-mediated Liver Injurymentioning
confidence: 99%